Training recollection in healthy older adults: clear improvements on the training task, but little evidence of transfer - Stamenova, Vessela; Jennings, Janine M.; Cook, Shaun P.; Walker, Lisa A. S.; Smith, Andra M.; Davidson, Patrick S. R. (Frontiers in Human Neuroscience, 2014)
Normal aging holds negative consequences for memory, in particular for the ability to recollect the precise details of an experience. With this in mind, Jennings and Jacoby (2003) developed a recollection training method using a single-probe recognition memory paradigm in which new items (i.e., foils) were repeated during the test phase at increasingly long intervals. In previous reports, this method has appeared to improve older adults’ performance on several non-trained cognitive tasks. We aimed to further examine potential transfer effects of this training paradigm and to determine which cognitive functions might predict training gains. Fifty-one older adults were assigned to either recollection training (n = 30) or an active control condition (n = 21) for six sessions over two weeks. Afterward, the recollection training group showed a greatly enhanced ability to reject the repeated foils. Surprisingly, however, the training and the control groups improved to the same degree as one another in recognition accuracy (d’) on their respective training tasks. Further, despite the recollection group’s significant improvement in rejecting the repeated foils, we observed little evidence of transfer to non-trained tasks (including a temporal source memory test). Age and higher baseline scores on a measure of global cognitive function (as measured by the Montreal Cognitive Assessment tool) and working memory (as measured by Digit Span Backward) predicted gains made by the recollection training group members.